The effect of antihypertensive drugs on cognitive functions - Atoeva , Munisa; Abdullaeva , Guzal; Yusupova , Khafiza; Ibragimova , Iroda (CARDIOLOGY OF UZBEKISTAN, 2025)
According to the World Health Organization data, 1.13 billion people worldwide suffer from arterial hypertension, with only 21% under proper control. Dementia currently negatively affects the quality of life of 55 million people worldwide, with one new case recorded every 3.2 seconds. Analyzing the effects of antihypertensive medications on cognitive function and evaluating protective mechanisms against dementia development is currently considered one of the urgent issues. There is reliable evidence that the effects of antihypertensive medications on cognitive function are related not only to blood pressure reduction but also to independent neuroprotective mechanisms. Angiotensin receptor blockers reduce dementia risk by 12-26% compared to other antihypertensive medications. Calcium channel blockers demonstrate 17% greater neuroprotective effects compared to other drug classes. ARBs and calcium channel blockers possess the best neuroprotective properties and are considered preferable for cognitive function protection. These effects occur independently of blood pressure reduction mechanisms.